GROW-OUT PERFORMENCE OF PUNTIUS SARANA SARANA (HAM.) IN CARP POLYCULTURE SYSTEM - BORAH, BIBHA CHETIA (Journal of the Inland Fisheries Society of India, 2021)
The study deals with the performance of Puntius sarana sarana (Ham.) as a component of the six species composite carp culture system. The species was included in place of common carp (Cyprinus carpio) in view of its omnivorous feeding habit and bottom dwelling nature. The total production was higher in the control (with common carp) than the experimental culture (with P. sarana) due to low growth rate of the minor carp, however, comparative economics revealed 5.66% higher return. Growth rate of other five species of carps was higher in the experimental set by 1.08% on an average than the control, which indicated that inclusion of P. sarana did not have any adverse impact on the other carp species. Key words: Puntius sarana sarana, polyculture, monoculture, compatibility